The Hymn Gloria and Its Place in the Celebration of the Eucharist - Vlastimil Dufka (Religions, 2024)
Music is an essential part of human life, but it is also integral to the experience of faith. From its beginnings, music has been associated with religious expression and worship. One of the oldest Christian hymns is the hymn “Gloria in excelsis Deo”-“Glory to God in the highest”, which was originally a component of morning and evening prayer. Later, it became part of the Holy Mass and is still sung during the celebration of the Eucharist on Sundays and feast days. The aim of this study is to provide a comprehensive view of this precious hymn in terms of its historical use. The study pays special attention to the sources of the text of this ancient hymn. A theological analysis of the text is also an indispensable prerequisite for a deeper understanding. Finally, the study offers up-to-date guidelines for the hymn’s use today.